Literacy and development for the Orang Asli in Malaysia: What matters? - Renganathan, S. (Springer Netherlands, 2016)
This article explores the literacy practices of the indigenous Semai Orang Asli community in Malaysia. Literacy for the Orang Asli often centres on formal education and schooling and is hardly explored from a social and cultural perspective. In fact, researchers have paid barely any attention to Orang Asli oral and literate traditions nor their correlation between home and school literacy practices, and the relationship between literacy and development. Thus, taking an ethnographic perspective, this article looks at literacy as a social practice in a setting where Orang Asli social and cultural values are marginal; Semai is not a written language; and literacy is learned in Malay, the national language in Malaysia. It hopes to address central issues and debates regarding the complex relationship between literacy and development inherent in the âgreat divideâ: the binary division between orality and literacy, and literacy and illiteracy; and the asymmetry in power relations in the Orang Asli community context in Malaysia. Â© 2017, UNESCO IBE.